Disparity of Judge's Decision on Children Of Narcotics Crime Actors Study on Denpasar State Court Decision No. 3 / Pid.Sus.Anak / 2014 / PN.Dps. by Denpasar State Court Decision No. 14 / Pid.Sus.Anak / 2015 / PN.Dps. - Dudu Wawan Setiawan; Bambang Tri Bawono (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The problem of this research is Why the disparity between the criminal Denpasar State Court Decision No. 3 / Pid.Sus.Anak / 2014 / PN.Dps. by Denpasar State Court Decision No. 14 / Pid.Sus.Anak / 2015 / PN.Dps.? Whether due to the disparity of criminal child Narcotics Crimes between Denpasar State Court Decision No. 3 / Pid.Sus.Anak / 2014 / PN.Dps. by Denpasar State Court Decision No. 14 / Pid.Sus.Anak / 2015 / PN.Dps. ?The method used by researchers is normative juridical law approach and specification in this study were included descriptive analysis. Now sources and types of data in this study are primary data obtained from interviews with field studies Denpasar State Court Judge, and secondary data obtained from the study of literature. Data were analyzed qualitatively. The problems studied by the theory of Pancasila justice, law enforcement and progressive.Based on the results of research that Children judge anyone considering the Research Society (Litmas) Community Advisors (PK) from the Institute of Corrections (Bapas) that, as considered by the Child Justice in case number 14 / Pid.Sus.Anak / 2015 / PN.Dps. Children temporary Judge's decision in case number 3 / Pid.Sus.Anak / 2014 / PN.Dps. not considering it, should judge Children in case number 3 / Pid.Sus.Anak / 2014 / PN.Dps. PK Litmas Bapas expensive, because the perpetrators of the Child is the only user, but instead judge Children in case number 14 / Pid.Sus.Anak / 2015 / PN.Dps. considering Litmas PK Bapas, whereas perpetrators Children in this case proved to be a dealer. Disparities criminal perpetrators of criminal acts against children Narcotics between Denpasar State Court Decision No. 3 / Pid.Sus.Anak / 2014 / PN.Dps. by Denpasar State Court Decision No. 14 / Pid.Sus.Anak / 2015 / PN.Dps. implications for the protection of child neglect.Keywords: Children; Disparity; Narcotics; Decision; Crime Actor.